Eating behavior of students in relation to the offer available in the vicinity of the university campus - Teodora Dominteanu; Liviu Marian Matac; Nicholas Victor Julius Alexander; Codruța Daniela Pavel; Adrian Iacobini; Andreea Voinea (Amfiteatru Economic, 2025)
Eating behavior of students is a major concern given the prevalence of chronic diseases associated with unhealthy food preferences, such as ultra-processed foods, which are characterized by wide availability, extensive marketing and advertising efforts and affordable prices. At the same time, the proximity of the vendors of such food products to university campuses and the students' financial constraints make this type of consumption exacerbate the pressure on the health care system and generate long-term negative effects on the health of students, future contributors to the labor market. This study differs from previous research by using a multimodal methodological approach, analyzing the relationship between food supply and demand in the vicinity of the university campus. The investigation examines the correlation between students' food preferences with the distribution of food suppliers, providing a detailed insight into how accessibility, pricing, and commercial strategies influence food choices. The results of the study indicated a preferential consumption of ultra-processed foods over healthy foods due to both their lower cost and to the presence of numerous vendors selling such food products in the vicinity of the campus. It was also observed that healthy foods were consumed more frequently outside the hours spent at the university, suggesting that the food environment on campus can be influenced by the university through a specific strategy to raise awareness about the risks associated with the consumption of ultra-processed foods, thus, towards healthier eating. The study contributes significantly to our understanding of the impact of socio-economic and cultural factors on students' food preferences, offering insights into their vulnerability to ultra-processed food supply. In addition, it highlights the existing gaps in food policies and puts forward recommendations with the aim of promoting healthy eating behavior by means of diversifying the offer and optimizing accessibility for the consumption of healthy products. Furthermore, it enhances the body of literature in this particular field.
Keywords: I0; I1; I11; I12; I23; 330; Bucharest University of Economic Studies; Eating behavior; food supply; students; ultra-processed foods; university campus